Highly dispersed MnOx nanoparticles on shape-controlled SiO2 spheres for ecofriendly selective allylic oxidation of cyclohexene - Rao, Bolla Govinda; Sudarsanam, Putla; Rao, Tumula Venkateshwar; Amin, Mohamad Hassan; Bhargava, Suresh K.; Reddy, Benjaram M. (Catalysis Letters, 2020)
Shape-controlled metal nanomaterials are considered as a unique class of catalysts because of their synergistic size- and shape-dependent catalytic properties. This work reports the synthesis of a novel size- and shape-controlled catalyst, consisting of highly dispersed MnOx nanoparticles (average particle size of 4.5 nm) on shape-controlled SiO2 nanospheres (250-300 nm) for selective cyclohexene oxidation using air as the oxidant under solvent- and base-free conditions. The MnOx/SiO2 catalyst exhibited an excellent cyclohexene conversion (92%) with a high selectivity (96%) to the allylic products (2-cyclohexene-ol and 2-cyclohexene-one) under mild conditions, outperforming various SiO2 supported CoOx, FeOx, and CuOx catalysts. The better performance of shape-controlled MnOx/SiO2 nanocatalyst is due to high redox nature of Mn, uniform dispersion of smaller sized MnOx nanoparticles, and synergetic interaction between MnOx and SiO2 spheres, as evidenced by XPS and TEM studies. Further, the MnOx/SiO2 catalyst could be reused at least 5 times for selective cyclohexene oxidation with a negligible loss in its catalytic performance, indicating the excellent stability of shape-controlled metal nanocatalysts in organic synthesis under economically viable and mild conditions.
Keywords: Cyclohexene oxidation; MnOx nanoparticles; Shape-controlled catalyst; SiO2 nanospheres; Structure-performance relationship; Synergetic interaction